Clinical outcomes and impact of therapeutic intervention in patients with acute myeloid leukemia who experience measurable residual disease (MRD) recurrence following MRD‐negative remission. Issue 11 (8th September 2022) - Short, Nicholas J.; Macaron, Walid; Kadia, Tapan; Dinardo, Courtney; Issa, Ghayas C.; Daver, Naval; Wang, Sa; Jorgensen, Jeff; Nguyen, Daniel; Bidikian, Aram; Patel, Keyur P.; Loghavi, Sanam; et al.
Abstract : Recurrence of MRD in AML is associated with imminent relapse unless intervened upon. Change in chemotherapy regimen and/or immediate transplant improve outcomes.